Kegiatan Pengukuran Komposisi Tubuh Dalam Rangka Deteksi Dini Obesitas Pada Populasi Lanjut Usia - Limas, Peter Ian; Santoso, Alexander Halim; Warsito, Jonathan Hadi; Lumintang, Valentino Gilbert (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Body composition refers to the various components that make up a person's body weight, such as lean mass (muscle, water, bones, ligaments, and tendons) and fat mass. As we age, significant changes occur in body composition, including increased fat mass and decreased muscle and bone mass, which often leads to sarcopenic obesity. This condition, which is common in older adults, is associated with frailty, disability, metabolic syndrome, reduced survival rates in certain cancers, and osteopenia/osteoporosis. This activity uses the PDCA (Plan-Do-Check-Act) method to measure the body composition of elderly participants at Hana Nursing Home, South Tangerang. A total of 40 participants underwent body composition examinations. The examination results showed that the average total body fat, visceral fat, subcutaneous fat, and skeletal muscle mass were 36.7% each; 8%; 27.6%; and 20.7%. We need to carry out routine body composition checks for early detection to provide timely management, ultimately improving long-term public health. Keywords: Body Composition, Early Detection, Elderly, Obesity, Sarcopenia